Performance Development and Quality of Work Life - Srirat, Saksit; Sommanasak, Waraduang; Chulsutthi, Nualnapa; Imiwat, Prayoon (Journal of Public Administration Chiang Rai Rajabhat University, 2026)
The purpose of this article is to inspire ideas by presenting concepts related to the quality of work life and the development of organizational efficiency. The author outlines a structured approach to this study, covering the following aspects: the definition of quality of work life, the benefits of having a good quality of work life, the meaning of effective work performance, factors influencing organizational work efficiency, an analysis of the relationship between performance development and quality of work life, and a conclusion. this article aims to provide insights that encourage scholars and researchers to recognize the significance of these concepts and apply them to human resource development and the enhancement of organizational efficiency. The findings reveal new knowledge, indicating a close relationship between quality of work life and organizational efficiency. A good quality of work life has a direct impact on an organization’s operational performance, aligning with McKinsey’s 7S framework.